Design and assessment of lipase-CuO nanoparticle conjugates for enhanced antimicrobial efficacy against clinical pathogens - Eman M. Handak; Dina H. Amin; Mai M. Elhateir (BMC Biotechnology)
Abstract In the battle against clinical infections particularly the resistant pathogens, the creation of new antimicrobial drugs is essential. This study focuses on synthesis and characterization of Lipase-CuO nanoparticle conjugates in order to investigate their antibacterial efficiency. Lipase enzyme and CuO nanoparticles were synthesized biologically by specific selected fungal strains. Statistical optimization of lipase enzyme was done using a Plackett-Burman design giving two enhancement models for lipase production with increasing in productivity up to 143.43% (2800 U/ml). Copper oxide (CuO) nanoparticles were characterized using visual indication of greenish color formation, UV-vis spectrum analysis which revealed a strong peak at 300 nm. Also, CuO nanoparticles appeared as distinct, well-dispersed spherical particles with average size of 71.035 nm using TEM, while conjugate appears as large protein molecules linked to the nanoparticles. Also, using techniques like energy dispersive X-ray (EDAX) the resultant conjugates formation was confirmed as the elemental analysis approved its formation. The antimicrobial activity of Lipase-CuO nanoparticles conjugates was tested against a range of clinical pathogens. The results demonstrated a significant increase in antimicrobial potency compared to both CuO nanoparticles and lipase alone particularly against E. coli strain NRC B-3703 with remarkable increase of 373.6% and 75% followed by S. aureus with increase of 50 and 42.8%compared to that of individual CuO nanoparticles and lipase enzyme, respectively. These findings suggest that Lipase-CuO nanoparticle conjugates hold great promise as a novel antimicrobial strategy, offering a potential solution to combat bacterial infections, especially those caused by multidrug-resistant strains. The study highlights the importance of nanotechnology in enhancing the efficacy of traditional antimicrobial agents and opens new avenues for targeted antimicrobial therapies.